A survey of UK practice patterns in the delivery of intravitreal injections. (July 2015) - Samia‐Aly, Emma; Cassels‐Brown, Andrew; Morris, Daniel S.; Stancliffe, Rachel; Somner, John E. A.
Abstract Purpose To assess UK practice patterns related to the prescription of antibiotics before, during and after intravitreal injections, the location where injections are carried out and the qualifications of those administering the injections. Methods Every ophthalmology unit featured in the Royal College of Ophthalmologists (UK) training directory was contacted. A healthcare professional involved in giving intravitreal injections at each institution completed a questionnaire regarding local practice patterns. Results A response rate of 85% (115/136) was achieved. Seventy four percent of hospitals (85/115) gave take home antibiotics post intravitreal injection. Twenty three percent (26/115) of hospitals employed non‐medical healthcare professionals to administer injections and 83% (96/115) administered intravitreal injections in a dedicated clean room as opposed to an operating theatre. Conclusion Practice patterns for intravitreal injection vary considerably. Guidelines alone do not appear to be effective in reducing practices which are considered wasteful and other approaches need to be developed.